Infectious Disease Preparedness and Response in the Post-COVID-19 World - Dr. Bushra Sumra; Soomro Abdul (North American Journal of Engineering Research, 2022)
Significant gaps in the world's preparedness for infectious diseases were revealed by the COVID-19 pandemic, undermining the urgent need for improved, flexible public health systems that can handle pandemics in the future. The challenges exposed by COVID-19, the lessons learnt, and potential ways to strengthen the resilience of public health systems are the main topics of this paper's systematic review of recent research on infectious disease preparedness and response.To ensure a high standard of evidence, the methodological quality of included systematic reviews was assessed using AMSTAR 2 (A Measurement Tool to Assess Systematic Reviews), a validated tool for evaluating systematic reviews, particularly in health research. Because we only selected high-quality research that were published between 2020 and 2023, we were able to present a thorough and trustworthy summary of contemporary preparedness tactics. The review's conclusions point to serious deficiencies in a number of crucial areas, including public communication tactics, hospital infrastructure, vaccination distribution equity, and worldwide disease tracking systems. Delays in COVID-19 containment attempts were caused by a lack of quick and efficient monitoring systems, particularly in low- and middle-income nations with inadequate funding. Additionally, problems with healthcare capacity—like a shortage of critical care facilities, PPE, and trained personnel—highlight the urgent need for large infrastructure investment. The outbreak in developing areas was unneccesarily prolonged this was by prolonged vaccination distribution, which thereby exposed significant gaps in healthcare delivery systems and the need for equitable access. Based on current data, the evaluation identifies strategic suggestions to close these gaps. Future preparedness frameworks should incorporate digital health technologies, such as contact tracing apps and artificial intelligence-driven surveillance, since they have demonstrated their worth.Healthcare personnel are the key players in ensuring infectious disease control and are a key player in order to effectively handle public health emergencies. International cooperation, which may be formalised through a Global Pandemic Treaty, is essential for transparent data exchange, resource allocation, and timely response during outbreaks. The paper also highlights the role of communication and public education strategies in order to build trust and prevent public miscommunication and unnecessary unrest during medical emergencies. Proactive public health messaging, health literacy initiatives, and clear government communication are necessary to lower public uncertainty and ensure compliance with health directives. In light of the recent occurrences, the report provides a thorough overview of infectious disease preparedness and response tactics. This lays the groundwork for upcoming studies and legislative efforts to improve the security of global health. The lessons learnt during COVID-19 must motivate prompt, coordinated action to create a robust public health system that can manage and prevent pandemics in the future.